Alcohol and other drug use among Belgian workers and job-related consequences. Issue 9 (14th August 2019) - Lambrechts, Marie-Claire; Vandersmissen, Lieve; Godderis, Lode
Abstract : Objectives: This study aimed to obtain prevalence data on use of alcohol and other drugs (AOD) among Belgian workers, and to explore the associations between self-reported AOD use and job-related effects as experienced by workers, and the level of workers' well-being, respectively. Methods: In this cross-sectional study (2016), 5367 workers filled out a questionnaire including validated instruments such as the Alcohol Use Disorders Identification Test-Consumption (AUDIT-C). Job-related effects were defined as: being late at work, absenteeism, loss of productivity, injuries, conflicts with co-workers and sanctions by employers. Descriptive and multiple logistic regression analyses were performed. Results: Based on AUDIT-C, 39.1% of last year drinkers had an indication of problem drinking. The odds of experienced job-related effects was 3.6 (CI 2.86 to 4.60) times larger than the odds among workers without this indication. This ratio decreased to 3.2 (CI 2.52 to 4.11), controlling for language, gender, family context, level of education and sector. Respondents who used illicit drugs more frequently (>once a month) also had an increased risk for experienced job-related effects (OR 5.8; CI 2.87 to 11.84). Having a low level of well-being increased the risk for job-related effects due to psychoactive medication (OR 2.3, CI 1.10 to 4.91). Discussion: In this study, self-reported AOD use was associated with short-term job-related effects. This suggests that an AOD policy in different sectors is needed with respect for the organisational culture. Its focus should lie on prevention and early detection of AOD problems, and on the mental health of workers. Attention is required for the non-medical use of prescription drugs.